Penerapan Model Pembelajaran Kooperatif Two Stay Two Stray (TSTS) Mata Kuliah Mikrobiologi untuk Meningkatkan Aktivitas Belajar Mahasiswa Melalui Kegiatan Lesson Study Di Jurusan Pendidikan Biologi FKIP UNIPA - Insar Damopolii; I Iwan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Lesson study has been carried out on V semester students in microbiology courses in the Biology Education and Teaching and Education Faculty Study Program, University of Papua, in the odd semester of the 2017/2018 academic year. The lesson activity of this study aims to improve the process and quality of biology learning. The activities carried out were the activities of the lesson team of biological studies consisting of model lecturers and observers. Lesson Study activities are carried out as many as four open classes, each open class consists of four stages of activity, namely: plan, implementation, observation and reflection or see. Each stage of producing planning (Chapter Design, Lesson Design, RPS and assessment instruments). The learning process is carried out through the application of the Two Stay Two Stray type (TSTS) cooperative learning model. Data obtained through observations by observers. The results obtained in the open class activities show that: (1) increasing student activity, creativity and independence, (2) students' understanding of concepts that are considered difficult to improve, and (3) the quality of microbiology learning increases (4) Learning cooperative type TSTS through lesson study activities (LS) can enhance collaboration and discussion between members of the lesson study team in planning and implementing learning, as well as reflection on learning activities (5) Can improve lecturer professionalism because initially lecturer-centered learning turns into learning centered on college student